'Acceptability' of a new oral suspension formulation of mercaptopurine in children with acute lymphoblastic leukaemia. (June 2016) - Mulla, Hussain; Buck, Helen; Price, Lisa; Parry, Annie; Bell, Geoff; Skinner, Roderick
Aim: The aim of this questionnaire-based survey was to determine the 'acceptability' of Xaluprine®, a new oral liquid formulation of mercaptopurine, when administered chronically to children during the maintenance treatment phase of acute lymphoblastic leukaemia. Patients and methods: This was a single centre survey of children (aged 3 to 16 years) and their parents at a routine follow-up visit during the maintenance phase of acute lymphoblastic leukaemica treatment. The questionnaire probed for their views on overall acceptability such as taste, smell, incidences of vomiting, ease and willingness to take Xaluprine® on a daily basis, and utilised a 5-point facial hedonic scale (1 = bad, 5 = good) as well as open/closed questions. Results: Twenty-two children were recruited; 17 (77%) scored taste between 3 and 5 ('okay' to 'good') and 20 (91%) scored smell between 3 and 5. Only four children (18%) reported an aftertaste. Of the five children (23%) who scored taste as 1 or 2 ('bad'), three found taking all oral medicines difficult. Six children (27%) reported vomiting, but this was not considered related to Xaluprine®. Seven children (32%) sometimes complained that they did not want to take Xaluprine®; 15 (68%) never complained. In response to the question, 'How easy is it for you to take Xaluprine®?' 18 children (82%) reported that it was 'Easy all the time.' This was more favourable than other oral liquid medicines that they were taking concurrently. Conclusion: The results of this survey show that Xaluprine® has good overall acceptability in the paediatric population and suggests that Xaluprine® is an important, alternative, age-appropriate formulation of mercaptopurine.